Challenges in the Writing of Cordillera local histories - Florendo, Maria Nela B. (Journal of Philippine local history and heritage, 2015)
Local history has become an arena for re-claiming a past that has been dominantly colonial in both authorship and perspective. This paper focuses on the challenges of writing local histories of indigenous peoples, specifically of the Cordillera.